2014
DOI: 10.1016/j.ijid.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection amongst Arab Israeli women with hyperemesis gravidarum—a prospective, controlled study

Abstract: H. pylori does not seem to increase the likelihood of hyperemesis gravidarum in Arab Israeli women. However, given the high background prevalence of H. pylori in this population, a larger study is required to corroborate these findings. (MOH20110066).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…pylori is also involved in the pathogenesis of cancer and lymphoma of the stomach. 6 In developing countries, 70% to 90% of the population is infected by the bacteria, while in industrialized countries the prevalence is smaller, ranging between 25% and 50%. 4 Many methods of Helicobacter pylori testing exist.…”
Section: Authorship: All Authors Have a Substantial Contribution To T...mentioning
confidence: 99%
“…pylori is also involved in the pathogenesis of cancer and lymphoma of the stomach. 6 In developing countries, 70% to 90% of the population is infected by the bacteria, while in industrialized countries the prevalence is smaller, ranging between 25% and 50%. 4 Many methods of Helicobacter pylori testing exist.…”
Section: Authorship: All Authors Have a Substantial Contribution To T...mentioning
confidence: 99%
“…In the other hand Boltin et al, 2014 showed no statistical difference in the seropositivity of H.pylori between hyperemesis group 75% and control group 60.4% P value 0.30 [15] .…”
Section: Discussionmentioning
confidence: 78%
“…This study is the first study that evaluates the association between blood group and the incidence of hyperemesis gravidarum. Although it is already revealed that H. pylori infection is associated with blood group O, but other studies found no association between H. pylori infection and hyperemesis gravidarum [25].…”
Section: Discussionmentioning
confidence: 92%